Synthesis of a graft-copolymer adsorbent through a green route and studies on its interactions with chromium(iii) through active functional groups: kinetics and improved adsorption supported by SEM-EDX and AFM1. Issue 56 (19th June 2015) - Kanagaraj, J.; Panda, Rames C.; Sumathi, V.
<x xml:space="preserve">Abstract</x> A novel adsorbent for enhanced absorption of chromium(iii).